Tingkat Pengetahuan Orang Tua tentang Penanganan Hipertermia pada Anak di Puskesmas Pahandut - Vina Agustina; Karmilawati Karmilawati (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Background: Hyperthermia is an abnormally high body temperature caused by thermoregulatory dysfunction. High fever can lead to shock, which, if not treated promptly, can result in death. Hyperthermia in children is commonly caused by viral infections, excessive heat exposure, dehydration, allergies, and immune system disorders. Objective: To determine the level of parental knowledge regarding the management of hyperthermia in children at Pahandut Health Center. Method: This study used a questionnaire design with a sample of 31 respondents at Pahandut Health Center. Results: The research results showed the level of parental knowledge about hyperthermia management at Pahandut Health Center, with 31 respondents categorized as follows: 14 respondents (45%) had good knowledge, 14 respondents (45%) had sufficient knowledge, and 3 respondents (10%) had poor knowledge. Conclusion: The study highlights the importance of parental knowledge in preventing hyperthermia in children.